FOREWORD - Kuzmanovska, Dragana (PALIMPSEST / ПАЛИМПСЕСТ, 2016)
As a current dean of the Faculty of Philology at Goce Delchev University in Stip I would like to express my great satisfaction and appreciation to all the authors who chose to support the second issue of the international journal “Palimpsest” by submitting their papers which are part of their scientific achievements in the field of linguistics, literature and cultural studies. Our pleasure is even greater due to the fact that we have managed to gather prominent scientists, researchers, linguists, writers, teachers, translators, interpreters and language lovers worldwide who try to contribute to science through these papers.